1990
DOI: 10.1177/0267323190005001005
|View full text |Cite
|
Sign up to set email alerts
|

Videomalaise Revisited: Media Exposure and Political Alienation in West Germany

Abstract: The concept of `videomalaise' was first used in America in the 1970s to describe the dual phenomenon of a loss of trust in political institutions and individuals' increasing reliance on television as a means of obtaining political information. Could it be that the particular features of political programming caused political malaise? Using West German survey data, the research presented here tests the validity of the videomalaise thesis. No connection was found between political malaise and the contents of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
2
8

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 10 publications
3
32
2
8
Order By: Relevance
“…In this argument, greater exposure is associated with greater distrust. Contrary to some earlierAmerican work (cited above) and recent European studies (Holtz-Bacha 1990;Newton n.d.), we find no support for this proposition. This may well be due to differences in national culture and media settings or in the measurement of entertainment media exposure.…”
Section: Discussioncontrasting
confidence: 69%
“…In this argument, greater exposure is associated with greater distrust. Contrary to some earlierAmerican work (cited above) and recent European studies (Holtz-Bacha 1990;Newton n.d.), we find no support for this proposition. This may well be due to differences in national culture and media settings or in the measurement of entertainment media exposure.…”
Section: Discussioncontrasting
confidence: 69%
“…In our studies of voter learning, we also found that paying attention to campaign news on radio, on television, in televised debates, and on the internet was associated with higher levels of interest in a presidential campaign, which is contrary to some studies that have suggested that paying attention to news media causes people to become more cynical and less interested or involved in politics (the so-called 'videomalaise' hypothesis) (Patterson, 1993;Holtz-Bacha, 1990;Mutz and Reeves, 2005).…”
Section: Voter Learningcontrasting
confidence: 98%
“…As it seems, watching the news on public TV makes viewers better informed and more motivated to follow public affairs, more efficacious, and less cynical with regard to authorities and institutions (Holtz-Bacha, 1990;Schmitt-Beck, 1998;Holtz-Bacha and Norris, 2001;Aarts and Semetko, 2003;de Vreese and Boomgaarden, 2006;Schmitt-Beck and Voltmer, 2007). This may be a result of these newscasts' superior information quality which reflects the general quality requirements for all programming that public broadcasters must follow, as outlined by media laws, charters, and the like.…”
Section: Resultsmentioning
confidence: 99%